Efektivitas Kompres Dingin Terhadap Skala Dismenorea Remaja Putri di SMAN 2 Ngaglik Sleman Yogyakarta - Melania Wahyuningsih (HEALTH CARE : JURNAL KESEHATAN, 2021)
Dysmenorrhea is caused by an imbalance of the blood hormone progesterone which causes pain during menstruation. Dysmenorrhea can interfere the activities of young women. How to reduce the pain scale of dysmenorrhea that is cheap and effective with cold compresses. This study was a quasi-experimental pre and post design, to determine the effectiveness of cold compresses on the dysmenorrhoea scale. The intervention given was doing a cold compress of ice water 10-15 degrees Celsius for 15 minutes. The research sample is 20 young women who experience menstruation on the first day. The sampling technique used is quota sampling. Data analysis using Wilcoxcon test. The results of the median study on the dysmenorrhoea scale before cold compresses, and after cold compresses 5. Wilcoxon test p value 0.001. Cold compresses are effective for reducing the scale of dysmenorrhea in adolescent girls at SMAN 2 Ngaglik Sleman Yogyakarta.